INOVASI “AYAH HEBAT” MELALUI PROGRAM KAMPUNG KB DI KELURAHAN AIR DINGIN - Desi Muslimah; Geovani Meiwanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The “Ayah Hebat” innovation is an innovation program in the KB village. This ayah hebat program is in the Toddler Family Development (BKB) group. This innovation begins to empower fathers who have an important role in a family, making a "Ayah hebat" who is always there for their children, knows more about their children's growth and development and most importantly, establishes emotional closeness with children. This ayah hebat's innovation has existed since the change project from the BKKBN and began to be implemented in Air Dingin from the end of 2019 until now. The purpose of this research is to analyze the implementation of the ayah hebat innovation in KB Village as a pilot in Air Dingin Village and find out what are the obstacles to this "ayah hebat" innovation. This study uses a qualitative method with a case study approach and the required data, both primary and secondary data obtained through interviews and documentation, are then analyzed based on research problems. The results of this study indicate that: first, the "ayah hebat" innovation has not run optimally. Secondly, there are several obstacles, including the ayah hebat cadre understanding and social status that must be continuously guided, given training and understanding about the implementation of this innovation as well as providing convenience for the community, especially fathers. Keywords: Innovation, Ayah Hebat, Kampung KB